Internal locus of control, social support and academic procrastination among students in completing the thesis - Winda Liftiana Sari; Fuadah Fakhruddiana (International Journal of Evaluation and Research in Education (IJERE), 2019)
The basis of this study was to determine the relationship between internal locus of control and social support with students' academic procrastination in completing their thesis. This study is using correlational sampling technique and the research samples taken from quota sampling technique are 80 college students who are in the process of completing the thesis. The measuring instrument is the Academic Procrastination Scale in completing the thesis, Internal Locus of Control Scale and Social Support Scale. The regression analysis result that there is a very significant correlation between internal locus of control and social support with academic procrastination of the students in completing the thesis. Further analysis showed that there is a very significant negative correlation between internal locus of control with academic procrastination. This means that the lower level of internal locus of control, the higher level of academic procrastination in completing a thesis, and vice versa. Likewise, there is a very significant negative correlation between social support and academic procrastination in completing a thesis. This result means that the lower level of social support, the higher level of academic procrastination in completing a thesis, and vice versa.